2011
DOI: 10.1111/j.1472-765x.2011.03004.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of ochratoxin A-producing Aspergillus section Nigri strains from California raisins

Abstract: Aims:  To determine incidence and levels of ochratoxin A (OTA) in California raisins and to isolate and characterize OTA‐producing fungi from California raisin vineyard populations. Methods and Results:  Forty raisin clusters sampled from four California vineyards in the San Joaquin Valley were analysed for OTA content using immunoaffinity and HPLC methods. OTA was detected in 93% of the samples, at levels from 0·06 to 11·4 ng g−1. From these raisin samples, a total of 400 strains of Aspergillus were isolated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 32 publications
1
29
0
Order By: Relevance
“…Ochratoxin A (OTA) is of public health concern because it is nephrotoxic, carcinogenic, immunesuppressive, teratogenic, hepatotoxic and cytotoxic (Palumbo et al 2011). Since OTA could cause cancer in humans, it was classified in group 2B by the International Agency for Research on Cancer (IARC 1993).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ochratoxin A (OTA) is of public health concern because it is nephrotoxic, carcinogenic, immunesuppressive, teratogenic, hepatotoxic and cytotoxic (Palumbo et al 2011). Since OTA could cause cancer in humans, it was classified in group 2B by the International Agency for Research on Cancer (IARC 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Penicillium (P. verrucisum and P. viridicatum) genera (Iha et al 2009;Palumbo et al 2011;Kuang et al 2012). Ochratoxin A (OTA) is of public health concern because it is nephrotoxic, carcinogenic, immunesuppressive, teratogenic, hepatotoxic and cytotoxic (Palumbo et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Ten percent of 264 sultana sample in Turkey were contaminated over than EU regulatory limits (Meyvaci et al 2005). Palumbo et al reported that OTA is a common contaminant of raisin, but average levels for dried fruit are much lower than EU recommends legal limits (Palumbo et al 2011).…”
Section: Introductionmentioning
confidence: 97%
“…Dried vine fruits (raisins, sultanas and currants) contribute to the total dietary exposure to OTA [7,8]. Thus, the European Union has established regulatory levels in order to control the presence of OTA in cereals, grape and coffee-derived products, raisins and other dried vine fruits [9,10].…”
Section: Introductionmentioning
confidence: 99%